Jurisdicción especial indígena en el departamento del Chocó (2001)
The present work of degree has as an objective interest to the development and coexistence of the indigenous social environment, its laws, the scope of limits and harmonization of the national legal order in the department of chocó. These populations face the problem of the loss of the territories of their ancestors, they live with the threat of losing their cultural identity; they have been violated even in their most basic rights, a situation that is palpable in the ethnic peoples of the department of chocó. We also determined that the indigenous people in the department of chocó, like those of the rest of the country, have undergone profound changes in the last decade, which reflect the form of articulation, presence and regional and local participation in the political, constitutional and normative levels. That have recognized indigenous rights, ranging from the right to equality to the right of difference based on the cn, materializing in the preamble of the same cultural wealth and establishing a multi-ethnic country and pluricultural.